Event-Based Control System Suitable for High-Precision Pulsed Current Source Applications with Improved Switching Behavior - Penovi, Emiliano (2015)
This work presents a control system suitable for high-precision pulsed current sources. The proposed control system is based on the detection of events so as to define changes in the power converter state to produce the required current waveform with a good dynamic response. Additionally, this control system is designed to regulate the flat-top current with a well-defined precision. In order to mitigate the effect of the measurement noise, an estimation algorithm for the controlled current is incorporated. This algorithm generates a filtered version of the controlled variable without affecting the control dynamics. The use of the estimated current allows to improve the detection of the events and to avoid an increase in the number of commutations due to possible erratic comparisons. Then, the estimator gains are tuned by using genetic algorithm techniques to optimize the root-mean-square value for a typical pulse. Furthermore, in order to independently perform the required set of tasks, the proposed control system is implemented by using a digital platform based on a field-programmable gate array. Additionally, due to the demanding precision in these applications, different considerations regarding its implementation, such as the digital wordlength, binary point position, rounding method, and overflow behavior, have been taken into account. Experimental results obtained from the application of the proposed control system to a laboratory prototype are presented.